2022
DOI: 10.1111/irv.13067
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mortality associated with seasonal influenza among adults aged 65 years and above in China from 2011 to 2016: A systematic review and model analysis

Abstract: Background: Estimation of influenza disease burden is crucial for optimizing intervention strategies against seasonal influenza. This study aimed to estimate influenzaassociated excess respiratory and circulatory (R&C) and all-cause (AC) mortality among older adults aged 65 years and above in mainland China from 2011 to 2016.Methods: Through a systematic review, we collected influenza-associated excess R&C and AC mortality data of older adults aged 65 years and above for specific cities/provinces in mainland C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The cost-per-episode of influenza illness ranged widely across studies (Fig 2). Twenty-four studies presented data about cost-per-episode, representing 8 UMICs (China [31][32][33][34][35][36][37][38][39], Colombia [40,41], Kazakhstan [42], Mexico [43], Panama [44], Romania [42], South Africa [45,46], and Thailand [47]), 6 LMICs (China [based on classification during study period] [48], El Salvador [44], India [49], Kenya [50], Ukraine [42], and Vietnam [51,52]), and 2 LICs (Bangladesh [53] and Mali [54]) (S4 Table ). Among the general population, the total cost-per-episode for outpatient visits, inclusive of direct and indirect costs, ranged from $6.24 to 155.92 (2022 US$); the total cost-per-episode for hospitalizations ranged from $106.85 to 1,617.14.…”
Section: Cost-of-illness Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-per-episode of influenza illness ranged widely across studies (Fig 2). Twenty-four studies presented data about cost-per-episode, representing 8 UMICs (China [31][32][33][34][35][36][37][38][39], Colombia [40,41], Kazakhstan [42], Mexico [43], Panama [44], Romania [42], South Africa [45,46], and Thailand [47]), 6 LMICs (China [based on classification during study period] [48], El Salvador [44], India [49], Kenya [50], Ukraine [42], and Vietnam [51,52]), and 2 LICs (Bangladesh [53] and Mali [54]) (S4 Table ). Among the general population, the total cost-per-episode for outpatient visits, inclusive of direct and indirect costs, ranged from $6.24 to 155.92 (2022 US$); the total cost-per-episode for hospitalizations ranged from $106.85 to 1,617.14.…”
Section: Cost-of-illness Studiesmentioning
confidence: 99%
“…Seven of the 23 studies reported a national economic burden of influenza illness for either the general population or specific SAGE target groups (Table 2), representing 3 UMICs (China [39], Romania [42], and South Africa [45,46]), 2 LMICs (Kenya [50] and Ukraine [42]), and 1 LIC (Bangladesh [53]). Total annual costs of influenza illness in studies evaluating the general population (no specified SAGE target group) were equivalent to 0.02% to 0.19% of the national GDP and 0.32% to 7.16% of the national health expenditure; costs for any single target group were <0.01% to 0.02% of the national GDP and 0.01% to 0.42% of the national health expenditure.…”
Section: Plos Medicinementioning
confidence: 99%